Freeze-thaw-stable high internal phase emulsions stabilized by soy protein isolate and chitosan complexes at pH 3.0 as promising mayonnaise replacers. (June 2022) - Huang, Zhi-Xuan; Lin, Wei-Feng; Zhang, Yin; Tang, Chuan-He
Graphical abstract: Highlights: A kind of high-freeze-thaw-stability high internal phase emulsions (HIPEs) at pH 3.0 was successfully fabricated. Such HIPEs were stabilized by complexes of heated soy protein isolate (SPI) and chitosan at pH 3.0. Increasing the chitosan ratio in the complexes facilitated the HIPE formation and stability. The good freeze-thaw stability was largely associated with the strong steric stabilization of chitosan. The as-formed HIPEs at pH 3.0 exhibited a promising potential as mayonnaise replacers. Abstract: The development of cholesterol-free mayonnaise has attracted increasing interest in the food colloid field, due to the potential health concerns as a result of consumption of cholesterol-rich mayonnaise. One effective strategy in this regard is to substitute or partially substitute egg yolk with other organic emulsifiers and stabilizers, without affecting the quality of the product. In the work, we reported an effective strategy to fabricate high freeze-thaw-stability high internal phase emulsions (HIPEs), using complexes of a heated soy protein isolate (SPI) and chitosan (CS) at pH 3.0 as the emulsifiers and stabilizers. The SPI/CS complexes, formed even at a very low CS-to-SPI ratio, e.g., 1:10, showed a high capacity to stabilize HIPEs with a high freeze-thaw stability. Increasing the CS-to-SPI ratio in the complexes resulted in a progressive strengthening of gel network in the corresponding HIPEs, together with a gradual improvement of emulsification performance. The gel network of the HIPEs stabilized by the SPI/CS complexes was mainly maintained by the inter-droplet noncovalent interactions involving the CS molecules. The presence of CS also progressively increased the percentage of adsorbed proteins at the interface, and decreased the surface coverage of proteins at the interface. The high freeze-thaw stability of such HIPEs might be unrelated to the ice crystal formation during the freezing, and was more likely associated with the strong steric repulsion contributed to the adsorbed CS molecules between different droplets. The results indicated that the complexation of heated SPI and CS could provide an effective strategy to facilely fabricate outstanding freeze-thaw-stability HI PEs as potential mayonnaise replacers.